(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
Because the world is becoming a planet where speed plays a much bigger role than only one generation ago, information is gained at almost the speed of light. Although is not seen as strange phenomenon anymore, the fact remains that technology has developed so drastically that it is almost unthinkable that a person of sixty years old today started her live without television, computer, internet, and perhaps, also without a telephone. In the process literature and language are disciplines that are drastically influenced, apart from the fact that 93% of all language is non-verbal. Images are becoming a most important part of communication and influence us cognitively and emotionally. Images also accelerate and increase our level of comprehension. Therefore visual literature is becoming an integral part of learning. In this article, the Afrikaans comic Asterix die Galliër is investigated, and it is argued that a comic can serve as a subgenre in the main stream of literature. Visual and verbal language are compared and common entities in the syntax, morphology and lexicon are identifi ed. It is concluded that the combined process of reading text and seeing images is essential for learning and rational thinking. Visual literature should therefore not be neglected as a source of academic training.